2019
DOI: 10.56093/ijas.v89i12.96279
|View full text |Cite
|
Sign up to set email alerts
|

Screening of germplasm of Abelmoschus against biotic stresses

Abstract: Okra [Abelmoschus esculentus (L.) Moench] is an important vegetable of which India is the leading producer, but its yield potential is hampered due to Bhendi Yellow Vein Mosaic Virus (BYVMV) disease and insect pests like whitefly, leafhopper, and shoot and fruit borer. The present study was done to identify the stable sources of resistance. Total 44 accessions of 6 wild Abelmoschus species and 2 check cultivars of A. esculentus (Pusa Sawani and Pusa A-4) were screened under natural field conditions at Division… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…C 1 Arkamosc (variant) 750-02 produced fruits like A. moschatus, confirming the dominance of genes from the wild parent. As A. moschatus, a perennial species, is reported to be tolerant to other multiple biotic stresses such as powdery mildew, jassids, whitefly, fruit, and shoot borer (Badiger and Yadav, 2019;Yadav et al, 2019), it can be utilized in multiple pest and disease resistance breeding . The perennation tendency and profuse-bearing habit of amphidiploids can also be exploited for selecting segregants to be used as a home garden vegetable, as a single plant in the kitchen garden can suffice the okra requirement of a family throughout the year.…”
Section: Selfed Amphidiploid Derivativesmentioning
confidence: 99%
“…C 1 Arkamosc (variant) 750-02 produced fruits like A. moschatus, confirming the dominance of genes from the wild parent. As A. moschatus, a perennial species, is reported to be tolerant to other multiple biotic stresses such as powdery mildew, jassids, whitefly, fruit, and shoot borer (Badiger and Yadav, 2019;Yadav et al, 2019), it can be utilized in multiple pest and disease resistance breeding . The perennation tendency and profuse-bearing habit of amphidiploids can also be exploited for selecting segregants to be used as a home garden vegetable, as a single plant in the kitchen garden can suffice the okra requirement of a family throughout the year.…”
Section: Selfed Amphidiploid Derivativesmentioning
confidence: 99%
“…C 1 Arkamosc (variant) 750-02 produced fruits like A. moschatus, confirming the dominance of genes from the wild parent. As A. moschatus, a perennial species, is reported to be tolerant to other multiple biotic stresses such as powdery mildew, jassids, whitefly, fruit, and shoot borer (Badiger and Yadav, 2019;, it can be utilized in multiple pest and disease resistance breeding (Badiger et al, 2023). The perennation tendency and profuse-bearing habit of amphidiploids can also be exploited for selecting segregants to be used as a home garden vegetable, as a single plant in the kitchen garden can suffice the okra requirement of a family throughout the year.…”
Section: Selfed Amphidiploid Derivativesmentioning
confidence: 99%
“…Waalk. was reported as one of the most prominent species exploited worldwide as a source of resistance/tolerance to YVMV, jassids, and fruit borer (Gangopadhyay et al, 2016;Badiger and Yadav, 2019;Patel et al, 2021). Santhiya et al (2022) also reported the promising accessions of A. moschatus (IC141055), A. tetraphyllus (IC90476-1), and A. caillei (Sikkim), which showed very low incidence of YVMV disease and no incidence of ELCV disease under natural epiphytotic screening.…”
Section: Introductionmentioning
confidence: 99%